MENGANALISIS VARIAN PRODUK, PROMOSI, HARGA, BRAND IMAGE TERHADAP LOYALITAS PELANGGAN APOTEK RIZAL BEKASI DI ERA PANDEMI COVID-19 - Rahmi Rosita; Retno Setya Budiasningrum; Nurul Giswi Karomah; Ria Estiana (POLITEKNIK LP3I JAKARTA, 2021)
The Covid-19 pandemic that has hit Indoensia for almost two years has caused changes in various aspects of life, especially having a significant impact on the public health aspect, thus demanding that people improve their health to be resilient to the threat of disease. This study aims to analyze the influence of product variants, promotions, prices,brand image on customer loyalty at the Rizal Bekasi Drug Store during the covid19 pandemic era. The research method used is descriptive qualitative method, with primary and secondary data sources from research results. The questionnaires were distributed using purposive sampling technique (samplingwith certain considerations), as many as 100 respondents. The instrument test was carried out with a Likert scale of 1 to 5 points using SPSS version 20. The results showed that 1. Product variants had a positive and significant effect on customer loyalty, 2. Promotion had a positive and significant effect on customer loyalty, 3. Price had a positive and significant effect on customer loyalty, 4. Brand image has a positive effect on customer loyalty. Keywords: Product Variants, Promotion, Price, Barnd Image, Customer Loyalty